Effects of blood pressure unawareness and poor adherence to antihypertensive drugs on outcomes of cerebrovascular accidents among patients with their first-ever stroke. Issue 3 (12th March 2023) - Bawand, Rashed; Ghiasian, Masoud; Khazaei, Mojtaba; Samadyan, Mustapha; Moradi, Abbas
Abstract : Aims: Our main target was to investigate the relationship of blood pressure (BP) unawareness and poor antihypertensive drug adherence with the clinical outcomes of the stroke including hospitalization time, degree of disability, and mortality rate. Methods and results: In this cross-sectional study, we evaluated 530 eligible patients (male = 313; female = 217), aged 18 years and older who had a proven diagnosis of nontraumatic first-ever stroke and were referred to the Shahid Beheshti Hospital of Hamadan, Iran, during the period from March 2019 to September 2021. The prevalence of BP unawareness was 19.6%, and 31.8% of antihypertensive drug users (14.3% of all studied population) had poor drug adherence, in which, older age, male gender, marriage, rural residence, and smoking were associated with the lack of appropriate drug adherence. There was no significant difference between patients with diverse stroke types (ischemic or hemorrhagic) from the points of BP awareness and adherence to antihypertensive drugs; nevertheless, patients with a positive history of cardiac diseases had a significantly higher awareness of their BP status ( P = 0.037). BP unawareness was associated with poor clinical prognosis, and could significantly increase stroke mortality ( P = 0.001) and disability ( P < 0.001) rates as well as the duration of hospitalization ( P < 0.001). Moreover, those who survived the stroke (modified Rankin Scale < 6) had the highest odds to be aware of their BP status (adjusted odds ratio [AOR] = 2.380 [95% confidence interval [CI] = 1.39–4.07]). Additionally, nonsmokers (AOR = 7.740), urban residents (AOR = 3.314), and literate patients (AOR = 2.092) had the highest odds of having appropriate drug adherence. Conclusion: Stroke mortality and morbidity rates can be significantly modified by persuading people to monitor their BP regularly and maximize antihypertensive medication adherence. In the meantime, increasing the literacy level in society and reducing the smoking rate can play important roles in achieving these goals. Abstract :